A 43-year-old man with recurrent spontaneous hypoglycemia - Islam, Md Hasanul; Rahman, Md Ashiqur; Khan, Murshed Ahamed; Mahjabeen, Samira; Mustari, Marufa; Fariduddin, Md (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2024)
Insulin autoimmune syndrome (IAS) is a rare hypoglycemic disorder characterized by recurrent episodes of fasting or late post-prandial hypoglycemia with a very high level of insulin and positive insulin antibody. We are reporting a case of recurrent episodes of spontaneous hypoglycemia in a 43-year-old male with biopsy-proven autoimmune hepatitis. After a thorough evaluation, he was found to have endogenous hyperinsulinemia. As there was no apparent cause of endogenous hyperinsulinemia, he was evaluated for insulin antibody which was found to be raised. A diagnosis of IAS was made, and he was put on a small frequent meal with tab diazoxide, and he improved. Although it is an uncommon disease, it should be kept in the differential diagnosis of spontaneous hypoglycemia. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2024;3(2): 71-74